2011
DOI: 10.1038/bjc.2011.425
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, ignorance and priorities for research in key areas of cancer survivorship: findings from a scoping review

Abstract: Background:Patients who have completed initial cancer treatment (cancer survivors) have been relatively neglected. We need data to help us better understand the needs of this group and to underpin evidence-based service development.Methods:Scoping reviews of research published in the last two decades focussing on the problems faced by cancer survivors, and the effectiveness of interventions for these problems were undertaken. The aim was to identify what we know, what we do not know and opportunities where res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 6 publications
1
57
0
1
Order By: Relevance
“…However, participants often realised that their 'new normal' involved reduced or no employment. Although it is acknowledged that returning to a job held before a diagnosis of cancer is not straightforward (Hubbard et al, 2010;Richardson et al, 2011), we found no specific discussion of it for people diagnosed with a poor prognostic cancer. Nevertheless, as so many of our participants were keen to return to paid work, it is an important factor and one which becomes more significant to both individuals and society as survival continues to increase (Bradley and Bednarek, 2002) and Tangka et al (2013) argue that it should be included in measures of cancer's overall effect in a population due to its huge impact on employers.…”
Section: A New Normalmentioning
confidence: 73%
“…However, participants often realised that their 'new normal' involved reduced or no employment. Although it is acknowledged that returning to a job held before a diagnosis of cancer is not straightforward (Hubbard et al, 2010;Richardson et al, 2011), we found no specific discussion of it for people diagnosed with a poor prognostic cancer. Nevertheless, as so many of our participants were keen to return to paid work, it is an important factor and one which becomes more significant to both individuals and society as survival continues to increase (Bradley and Bednarek, 2002) and Tangka et al (2013) argue that it should be included in measures of cancer's overall effect in a population due to its huge impact on employers.…”
Section: A New Normalmentioning
confidence: 73%
“…This is partly because there is a time lag between research and its integration into practice, but also because it is more difficult to demonstrate changes to clinical practice as a result of research. Nevertheless, some influences are being detected, for example, on policy17 and in clinical guidelines for supportive care in multiple myeloma,18 and National Cancer Survivorship Initiative participating in the NCRI rapid review to determine research priorities for cancer survivorship 19 20…”
Section: Ceco's Building Research Capacity Activitiesmentioning
confidence: 99%
“…This has been achieved through the promotion of evidence-based practice to benefit patient care that has also been relevant to the decision making of practitioners and policy makers. For example, research on Cancer Survivorship has informed the emerging strategic direction taken by Macmillan Cancer Support and the National Cancer Survivorship Initiative 19 26. Research and scholarship on decision making for frail older people who lack capacity has informed a Council of Europe Symposium on medical decision making at the end of life,27 and the development of guidance for health and social care staff about decision making and advance care planning in life-limiting illness 28.…”
Section: Ceco's Building Research Capacity Activitiesmentioning
confidence: 99%
“…Performing physical activity has been shown to reduce the risk for cancer recurrence and chronic disease [18] and is suggested in several guidelines and recommendations [9, 10, 12, 19 -21]. The evidence base for the long-term effects of rehabilitation is rather small because the follow-up duration is usually short [22].…”
Section: Introductionmentioning
confidence: 99%